(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Academic success is a crucial tool for reaching one’s goals and fostering all-around growth ina youngster. The main aim of the study is to Students Towards Behavioural Factor Of E-Learning AndTraditional Learning. The experimental design is the plan for the experiment that will be used to test thehypotheses and draw reliable findings regarding the connection between the independent anddependent variables. Students in their last class of secondary school are shown to have the samebehavioral attitude toward E-learning, regardless of gender.